2022
DOI: 10.3389/fenrg.2021.795513
|View full text |Cite
|
Sign up to set email alerts
|

A Dynamic and Cooperative Control Strategy for Multi-Hybrid Energy Storage System of DC Microgrid Based on SOC

Abstract: With the increasingly serious crisis of fossil energy and environmental pollution, clean renewable energy becomes the inevitable choice of energy structure adjustment. The instability of output power of distributed renewable energy system greatly affects the operation of DC microgrid. The hybrid energy storage system (HESS) composed of High-Energy Battery (HEB) and High-Power Battery (HPB) can solve the above problems. Thus, this paper proposes a dynamic and cooperative control strategy for multi-HESS based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…In reference [3], an improved E index U/I droop control for energy storage was constructed. Reference [4] balances different energy storage SOCs based on LPF method and droop method. In reference [5], an improved droop control was proposed considering SOC and load power demand.…”
Section: Introductionmentioning
confidence: 99%
“…In reference [3], an improved E index U/I droop control for energy storage was constructed. Reference [4] balances different energy storage SOCs based on LPF method and droop method. In reference [5], an improved droop control was proposed considering SOC and load power demand.…”
Section: Introductionmentioning
confidence: 99%
“…Several important studies on this topic have been reported in the literature (Tummuru et al, 2015a;Tummuru et al, 2015b;Karimi et al, 2017;Manandhar et al, 2019;Xu et al, 2020;Hosseini et al, 2021;Jiang et al, 2021;Li et al, 2022). However, these studies have focused on isolated situations with DC link for RES-grid connected HESS or DG resources.…”
Section: Introductionmentioning
confidence: 99%
“…In MG management systems, a coordinated SoC control strategy is implemented to stabilize the bus frequency and voltage amplitude of MGs based on a model predictive control algorithm for DG and ESS units. If one communication link fails, the whole system is out of synchronization, so ESS and RES are coordinated by centralized management control (Li et al, 2022). According to the EMS proposed in (Xu et al, 2020), power can be injected or withdrawn from the grid based on changes in DC and AC load and changes in RES power.…”
Section: Introductionmentioning
confidence: 99%